Effect of dengue hemorrhagic fever on thrombomodulin level - Hendra Widjaja; Max F. J. Mantik (Indonesian Pediatric Society Publishing House, 2009)
Background Thrombocyte and endothelial cells play an important role in dengue hemorrhagic fever pathogenesis. Thrombomodulin is a part of glycoprotein membrane in endothelial cells. Therefore, thrombomodulin level will increase if endothelial cells disruption occurs. Objective To acknowledge the correlation between the degree of dengue hemorrhagic fever and thrombomodulin level. Methods This was a cross-sectional study. Subjects were hospitalized pediatric patients with age ranging from one to 13 year old in pediatric ward at Pro£ Dr. R.D. Kandou Hospital, Manado, who had fever. Three milliliters of blood were taken from vein, and were divided for two tests which were routine blood analysis and thrombomodulin analysis. Different data resulted from the dengue hemorrhagic fever group were processed, and analyzed statistically using F Test and LSD (least significant difference) test. The relation between dengue hemorrhagic fever and thrombomodulin was analyzed with Spearman correlation coefficient. Results There was a significant result in the difference of thrombomodulin level on four dengue hemorrhagic fever groups which were classified according to the severity of dengue hemorrhagic fever. There was a very significant positive correlation between the severity of dengue hemorrhagic fever and thrombomodulin level in detecting endothelial cells impairment. Conclusion Thrombomodulin level can be used as a marker to detect endothelial cells impairment in dengue hemorrhagic fever. Higher grade of dengue hemorrhagic fever will have higher thrombomodulin level.